The effects of leader succession and prior leader experience on postsuccession organizational performance - Desai, Malay N.; Lockett, Andy; Paton, David (Wiley, 2016)
In this article we strive to reconcile equivocal findings about the effects of top leader succession and prior leadership experience on postsuccession organizational performance. In doing so, we draw on insights from theories of human capital, learning, and asymmetric information to better understand the conditions under which leaders increase or decrease postsuccession performance. Employing a sample of 119 newly appointed leaders in the English Premier League (1996–2010), we find the following results. First, relating to the succession event, outside leaders that directly move between leadership positions are associated with higher postsuccession performance while the departure of a prior leader to a leadership position in another organization has a negative effect on postsuccession performance. Second, relating to prior leadership experience, leaders with domestic top leader experience are associated with lower postsuccession performance, while leaders with foreign top leader experience are associated with higher postsuccession performance.